2012
DOI: 10.4236/alc.2012.12002
|View full text |Cite
|
Sign up to set email alerts
|

Supportive care needs and health-related quality of life among Chinese lung cancer survivors

Abstract: Purpose: The purpose of this study was to explore the supportive care needs and health-related quality of life (HRQoL) of lung cancer survivors, and to identify the association between patient characteristics, HRQoL and supportive care needs. Method: This was a sub-study of a larger scale survey of cancer survivors' supportive care needs. A total of 48 lung cancer survivors were recruited from a regional teaching hospital, and a three-part structured questionnaire was used to collect 1) socio-demographic and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…After removal of duplicates, we screened titles and abstracts of 3236 and identified 61 as potentially relevant. Following assessment of the full text of these potentially relevant articles, we identified four studies involving patients with lung cancer that met our inclusion criteria (Chan et al, 2012;Giuliani et al, 2016;Pardon et al, 2011;Sanders et al, 2010). A further six studies were identified with mixed cancer populations; the lung cancer cohort from one of these was reported in an included study (Chan et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removal of duplicates, we screened titles and abstracts of 3236 and identified 61 as potentially relevant. Following assessment of the full text of these potentially relevant articles, we identified four studies involving patients with lung cancer that met our inclusion criteria (Chan et al, 2012;Giuliani et al, 2016;Pardon et al, 2011;Sanders et al, 2010). A further six studies were identified with mixed cancer populations; the lung cancer cohort from one of these was reported in an included study (Chan et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…There was some variation across the studies in the tools used to assess QoL and unmet needs (Table 1). Four studies of the six studies assessed patients' QoL using cancer specific tools (Chan et al, 2012;Giuliani et al, 2016;Sanders et al, 2010;Zhu et al, 2018). Molassiotis et al, used a single item, taken from the Cancer Survivors Survey of Need (Filsinger et al, 2011); in all cases a higher score represented a higher QoL.…”
Section: Measures Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…In western countries unmet needs were highest in psychological domain which is consistent with the findings of this study [ 36 , 42 , 43 ]. Whereas in Asian developing countries unmet needs were mostly related to health system information [ 17 , 44 47 ]. As a matter of fact, supportive care needs are the product of perspective of culture and interaction of psychology based on cultural context [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is acknowledged as an essential service, 1–93 % of cancer patients’ supportive needs have been consistently unmet [ 15 , 16 ]. There is growing evidence that the needs perceived by breast cancer patients and the support being provided by the healthcare professionals are diverse [ 8 , 17 , 18 ]. Hence, it is found that the breast cancer patients mostly suffer from physical, emotional, social, financial and psychological disturbances to a greater extent and unmet needs were highest in the post-treatment phase compared to the other phases of cancer continuum [ 10 , 15 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%